Incorporating ToxCast and Tox21 datasets to rank biological activity of chemicals at Superfund sites in North Carolina. (April 2017) - Tilley, Sloane K.; Reif, David M.; Fry, Rebecca C.
Abstract: Background: The Superfund program of the Environmental Protection Agency (EPA) was established in 1980 to address public health concerns posed by toxic substances released into the environment in the United States. Forty-two of the 1328 hazardous waste sites that remain on the Superfund National Priority List are located in the state of North Carolina. Methods: We set out to develop a database that contained information on both the prevalence and biological activity of chemicals present at Superfund sites in North Carolina. A chemical characterization tool, the Toxicological Priority Index (ToxPi), was used to rank the biological activity of these chemicals based on their predicted bioavailability, documented associations with biological pathways, and activity in in vitro assays of the ToxCast and Tox21 programs. Results: The ten most prevalent chemicals found at North Carolina Superfund sites were chromium, trichloroethene, lead, tetrachloroethene, arsenic, benzene, manganese, 1, 2-dichloroethane, nickel, and barium. For all chemicals found at North Carolina Superfund sites, ToxPi analysis was used to rank their biological activity. Through this data integration, residual pesticides and organic solvents were identified to be some of the most highly-ranking predicted bioactive chemicals. This study provides a novel methodology for creating state or regional databases of biological activity of contaminants at Superfund sites. Conclusions: These data represent a novel integrated profile of the most prevalent chemicals at North Carolina Superfund sites. This information, and the associated methodology, is useful to toxicologists, risk assessors, and the communities living in close proximity to these sites. Highlights: A comprehensive database of the prevalence and predicted biological activity of chemicals found at North Carolina Superfund sites is presented. Toxic metals remain highly prevalent at North Carolina Superfund sites. Integrating different types of data in chemical rankings provides more inclusive information to policy makers and can aid in better risk assessment. A novel methodology for characterizing the prevalence and biological activity of chemicals present at Superfund sites is proposed.